2020
DOI: 10.3390/ijms21197060
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Disorders and Mitochondrial Dysfunction: A Critical Review for Prospect Mitoprotective Strategies Based on Mitochondrial Nutrient Mixtures

Abstract: A number of aging-related disorders (ARD) have been related to oxidative stress (OS) and mitochondrial dysfunction (MDF) in a well-established body of literature. Most studies focused on cardiovascular disorders (CVD), type 2 diabetes (T2D), and neurodegenerative disorders. Counteracting OS and MDF has been envisaged to improve the clinical management of ARD, and major roles have been assigned to three mitochondrial cofactors, also termed mitochondrial nutrients (MNs), i.e., α-lipoic acid (ALA), Coenzyme Q10 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 138 publications
0
15
0
1
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity decreased mitochondrial content are hallmarks of aging and play an important role in promoting aging [92,93]. Increasing literature reported that resveratrol regulated the mitochondrial function, thus delaying the aging process.…”
Section: In Vitro Oocytes and Granulosa Cellsmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity decreased mitochondrial content are hallmarks of aging and play an important role in promoting aging [92,93]. Increasing literature reported that resveratrol regulated the mitochondrial function, thus delaying the aging process.…”
Section: In Vitro Oocytes and Granulosa Cellsmentioning
confidence: 99%
“…It is an essential cofactor in the mitochondrial aerobic metabolism and multienzyme complexes, being implied in the glucose conversion and energy production [8] and a potent antioxidant [9][10][11]. ALA displaying an excellent scavenging activity against the hydroxyl radical (HO•), with anti-inflammatory activity-by decreasing the tumor necrosis factor (TNF)-α, interleukin (IL)-1 beta (IL-1β), and IL-6 [12,13], performing an anti-aging activity [14] metal-chelating capacities and acting on the second messenger nuclear factor κB without any side effects [15]; almost meets all standards of a perfect anti-aging substance [15]. Consequently, the widespread use of ALA as a functional compound is increasing [16].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, performance on measures of executive attention and the cognitive-composite might then provide highly sensitive behavioral measures of cognitive aging and cognitive deficits associated with disorders that involve mitochondrial dysfunctions, such as those associated with disruptions to glucose homeostasis ( Section 3.1 ). These behavioral measures might also prove to be useful for the assessment of the efficacy of pharmacological treatments of mitochondrial disorders as a means to address age-related or disease-related cognitive decline [ 143 ].…”
Section: Implications For Study Of Aging and Dementiamentioning
confidence: 99%